What Do We Know about Barley miRNAs? - Volná, Adriana; Bartas, Martin; Pečinka, Petr; Špunda, Vladimír; Červeň, Jiří (International journal of molecular sciences, 2022)
Plant miRNAs are powerful regulators of gene expression at the post-transcriptional level, which was repeatedly proved in several model plant species. miRNAs are considered to be key regulators of many developmental, homeostatic, and immune processes in plants. However, our understanding of plant miRNAs is still limited, despite the fact that an increasing number of studies have appeared. This systematic review aims to summarize our current knowledge about miRNAs in spring barley (Hordeum vulgare), which is an important agronomical crop worldwide and serves as a common monocot model for studying abiotic stress responses as well. This can help us to understand the connection between plant miRNAs and (not only) abiotic stresses in general. In the end, some future perspectives and open questions are summarized.
Keywords: Plants; barley; miRNAs; Stress, Physiological; fyziologický stres; environmental stress; ječmen (rod); mikro RNA; regulation; plants; Hordeum; gene expression; rostliny; regulace genové exprese u rostlin; MicroRNAs; Gene Expression Regulation, Plant